Association study of MICA and MICB in Alzheimer's disease. - Quiroga, I; Lehmann, D; Barnardo, M; Fuggle, S; Cortina-Borja, M; Warden, DR; Smith, A (2009)
Following the replication of the association of the human leucocyte antigen (HLA) allele, HLA-B*07, with Alzheimer's disease (AD) in the cohort of the Oxford Project to Investigate Memory and Ageing (OPTIMA) in a previous study, we examined whether that association could be due to linkage disequilibrium with MICA or MICB alleles. We found a possible association of MICA*00801 heterozygotes with AD in subjects positive for the epsilon 4 allele of apolipoprotein E. This finding was supported by Hardy-Weinberg analysis, by stratified association analysis and by interaction analysis, but did not survive correction for multiple testing. In any case, these results do not explain our previously reported association of HLA-B*07 with AD.